Spindle cell squamous cell carcinoma of postcricoid region of hypopharynx: a case report of a rare tumour in uncommon location with atypical presenting complaint - Ali, Syed F.; Amjad, Marium; Atiqa; Dhanani, Rahim; Ashfaq, Zoonish; Arif , Basit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Spindle cell carcinoma (SpCC) is an aggressive subtype of squamous cell carcinoma characterized by a biphasic pattern with both sarcomatous spindle cell and epithelial squamous cell components. It accounts for less than 3% of all head and neck cancers, with a male predominance, presenting in the 5th to 6th decades of life. The larynx is the most commonly affected site, with dysphagia being the most frequently presenting complaint. Hypopharyngeal involvement is uncommon, particularly in the postcricoid region. We present a 55-year-old male with a complaint of bilateral neck swellings without dysphagia. An exophytic growth on the postcricoid region of the hypopharynx was evident on laryngoscopy, and histopathology confirmed SpCC. A computed tomography (CT) scan showed necrotic cervical nodes, and chemotherapy was initiated for treatment.